Harnessing University Strengths in Multisectoral Collaborations for Planetary Health. Issue 12 (23rd August 2018) - Passarelli, Simone; Canavan, Chelsey R; Paarlberg, Robert; Juma, Calestous; Akyeampong, Emmanuel; Fekadu, Habtamu; Golden, Christopher D; Gunaratna, Nilupa S; Jaacks, Lindsay M; Kennedy, Eileen; Madzorera, Isabel; McCann, James; et al.
Abstract: Although significant achievements in human health have been made globally, progress has been made possible, in part, through unconstrained use of natural resources. As the health of our planet worsens, human health is also endangered. Scholars and policymakers from diverse disciplines highlighted complex, multisectoral approaches for addressing poor dietary intake, over- and undernutrition, and chronic diseases in sub-Saharan Africa at the Agriculture, Nutrition, Health, and the Environment in Africa Conference held at Harvard University on 6–7 November 2017. A planetary health approach to addressing these challenges offers a unique opportunity to advance solutions for environmental and social factors that influence agriculture, nutrition, and overall health in the larger context of rapid population growth and transitions in food systems and livelihoods. This paper outlines 3 key avenues for universities to promote science at the intersection of public health and the environment in sub-Saharan Africa.